Exorcism and deliverance multi-disciplinary studies - Kay, William K. 1945- (Milton Keynes Paternoster, 2011)
Introduction Exorcism : multi-disciplinary perspectives Robin Parry -- The presence of evil and exorcism in the Old Testament Wonsuk Ma -- Deliverance and exorcism in the New Testament Graham Twelftree -- Deliverance and exorcism in the early church Andrew Daunton-Fear -- Deliverance and exorcism in the twentieth century James Collins -- Deliverance and exorcism in majority world Pentecostalism Allan Anderson -- Deliverance and exorcism in anthropological perspective Peter Versteeg -- Deliverance and exorcism in psychological perspective William K. Kay -- Deliverance and exorcism in philosophical perspective Phillip H. Wiebe -- Deliverance and exorcism in pop culture Lucy Huskinson -- Deliverance and exorcism in theological perspective 1 Is there any substance to evil? Nigel G. Wright -- 2 Possession and exorcism as New Testament evidence for a theology of Christ's supremacy Kabiro Wa Gatumu -- Demonology and deliverance : a practical-theological case study Mark Cartledge
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Exorcism; Aufsatzsammlung